Synthesis of macrocyclic precursors of the vioprolides. Issue 38 (18th September 2018) - Butler, Eibhlin; Florentino, Lucia; Cornut, Damien; Gomez-Campillos, Gonzalo; Liu, Hao; Regan, Andrew C.; Thomas, Eric J.
Abstract : Convergent syntheses have been developed of macrocycles that may be useful for the synthesis of vioprolide D. Preliminary studies have also been carried out into the introduction of the thiazoline and ( E )-dehydrobutyrine components. Abstract : The vioprolides are novel depsipeptides that have not been synthesized. However, they have been identified as important targets for synthesis because of their novel biological activities and challenging chemical structures. Following early work on the synthesis of a modified tetrapeptide that contained both the ( E )-dehydrobutyrine and thiazoline components of vioprolide D, problems were encountered in taking an ( E )-dehydrobutyrine containing intermediate further into the synthesis. A second approach to vioprolides and analogues was therefore investigated in which ( E )- and ( Z )-dehydrobutyrines were to be introduced by selenoxide elimination very late in the synthesis. A convergent approach to advanced macrocyclic precursors of the vioprolides was then completed using a modified hexapeptide and a dipeptidyl glycerate. In this work, it was necessary to protect the 2-hydroxyl group of the glycerate as its acetate and not as its 2, 2, 2-trichloroethoxycarbonate. Preliminary studies were carried out on the introduction of the required dehydrobutyrine and thiazoline components into advanced intermediates.